Metabolic Disturbances Induced by Sleep Restriction as Potential Triggers for Alzheimer’s Disease - García-Aviles, Jesús Enrique; Méndez-Hernández, Rebeca; Guzmán-Ruiz, Mara A.; Cruz, Miguel; Guerrero-Vargas, Natalí N.; Velázquez-Moctezuma, Javier; Hurtado-Alvarado, Gabriela (Frontiers in Integrative Neuroscience, 2021)
Sleep has a major role in learning and memory consolidation and metabolic function. Although it is known that sleep restriction increases the accumulation of amyloid β peptide (Aβ) and induces cognitive impairment associated with the risk to develop Alzheimer’s disease (AD), the mechanism behind these effects remains unknown. In this review, we will discuss how chronic sleep restriction induces metabolic and cognitive impairments that could result in the development of AD in late life. Here, we integrate evidence regarding mechanisms though which metabolic signals become disturbed after short or chronic sleep restriction in the context of molecular mechanisms associated to cognitive impairment, particularly in the accumulation of Aβ in the brain. Also, we discuss the role of the blood-brain barrier in sleep restriction with an emphasis in the transport of metabolic signals and Aβ clearance. This review presents the unexplored possibility that the alteration of peripheral metabolic signals induced by sleep restriction is responsible for cognitive deficit and, subsequently, are implicated in AD development.